Reinforced aortic root reconstruction for acute type A aortic dissection involving the aortic root - Qing-qi,Han (2013)
OBJECTIVE: There are debates regarding the optimal approach for AAAD involving the aortic root. We described a modified reinforced aortic root reconstruction approach for treating AAAD involving the aortic root. METHODS: A total of 161 patients with AAAD involving the aortic root were treated by our modified reinforced aortic root reconstruction approach from January 1998 to December 2008. Key features of our modified approach were placement of an autologous pericardial patch in the false lumen, lining of the sinotubular junction lumen with a polyester vascular ring, and wrapping of the vessel with Teflon strips. Outcome measures included post-operative mortality, survival, complications, and level of aortic regurgitation. RESULTS: A total of 161 patients were included in the study (mean age: 43.3 1 15.5 years). The mean duration of follow-up was 5.1 1 2.96 years (2-12 years). A total of 10 (6.2%) and 11 (6.8%) patients died during hospitalization and during follow-up, respectively. Thirty-one (19.3%) patients experienced postoperative complications. The 1-, 3-, 5-, and 10-year survival rates were 99.3%, 98%, 93.8%, and 75.5%, respectively. There were no instances of recurrent aortic dissection, aortic aneurysm, or pseudoaneurysm during the entire study period. The severity of aortic regurgitation dramatically decreased immediately after surgery (from 28.6% to 0% grade 3-4) and thereafter slightly increased (from 0% to 7.2% at 5 years and 9.1% at 10 years). CONCLUSION: This modified reinforced aortic root reconstruction was feasible, safe and durable/effective, as indicated by its low mortality, low postoperative complications and high survival rate.